Issue differential - multidimensional technique for measuring components of attitudes towards social-issues - Davis, E.E. (Economic & Social Studies, 1977)
The Semantic Differential (SD) technique, developed by Osgood, Suci and Tannenbaum (1957) is perhaps one of the most widely used instruments for tapping attitudes or perceptions towards a variety of objects. This is attested to by the fact that the basic reference to Osgood et al (1957), is perhaps one of the most (if not the most) frequently cited references in the social psychological literature.
Keywords: Semantic Differential (SD) technique; Sociology